Occupational Stress among the Women Graduate Teachers in the Northern Province of Sri Lanka - Selvarajan, P.; Manokar, P. (Sabaragamuwa University of Sri Lanka, 2010)
This study intends to identify the Occupational stress among the graduate school teachers in the Northern Province of Sri Lanka. Stress is an inevitable aspect in our day to day life. All people are inevitably exposed to various stressful situations. Poverty, unemployment, the threat of political, economic and social imbalances, and uncertainties lead to stress. Due to the current needs by every family, women are joining in the workforce in huge level. As such they have to perform and maintain a balance between familial and professional roles. Further, women staff are often confronted with additional pressure from both places in compared with men. Some researchers have found role difficulty and occupational stress were reported to be negatively and significantly associated with job satisfaction. In Sri Lanka also the women employees have been facing the problem of stress since they play dual roles in the work place as well as at home. The key problem associated with this research study is the reluctance to women graduate teachers to take over the managerial positions in schools and other educational offices due to the family responsibilities and this leads them to occupational stress. The objectives of the study are to understand the phenomenon of occupational stress among women graduate teachers; to identify the factors causing for stress; to determine the dimensions of occupational stress; to determine the level of occupational stress and the remedial actions to be taken to reduce the stress level in the work place. For this purpose 100 graduate teachers were selected in Northern Province of Sri Lanka by using simple random sampling method and the Descriptive Statistics were used to analyze the data. According to these analyses five dimensions were identified by authors such as current demands, control mechanisms, relationships, changes in the work place and support to determine the level of occupational stress. Findings show that different factors have caused and influenced on stress at various levels. Though the stated five dimensions influence on occupational stress, demands and control mechanisms play prominent role in determining high occupational stress among the women graduate teachers since, the graduate teachers in public schools were not given regular career guidance training. To practice the staff appraisal annually and support from all the other stakeholders (including the family members) are the significant factors to reduce the occupational stress among them.
Keywords: Family responsibilities; Northern province of Sri Lanka; Occupational stress; Women Graduate teachers